The Effect of Pressure on Electronic and Magnetic Properties of MnAs Crystal. (26th September 2013) - Moradiannejad, Farzad; Hashemifar, S. Javad; Akbarzadeh, Hadi
Abstract : The structural, electronic, and magnetic properties of MnAs crystal are studied. The WIEN2k code which uses a full-potential LAPW program based on density functional theory with GGA is used for the calculations. At first, the total energy of a MnAs crystal in different lattices is calculated and the corresponding E -V diagram is drawn for two different structures of MnAs. The effect of pressuring this crystal is determined. The calculations confirm that, MnAs has the NiAs-type structure at ambient pressure but transforms into the zinc-blend structure of a specific pressure value. Also, the electric field gradient (EFG) and hyperfine field (HFF) at the nuclear site of Mn and As are calculated. Finally, the effect of pressure on EFG and HFF is studied.